A new species of Phyllodactylus (Reptilia, Squamata, Gekkonoidea, Phyllodactylidae) from Isla de Guanaja in the Honduran Bay Islands - Mccranie, James R.; Hedges, S. Blair (Zootaxa, 2013)
Morphological and molecular analyses of the Phyllodactylus populations on the Honduran Bay Islands of Guanaja, Roatán, and Utila demonstrate that the Guanaja population is best treated as a species distinct from the two other island populations. Thus, P. palmeus is restricted in distribution to Roatán and Utila islands and the Cayos Cochinos and a new species name is provided for the Guanaja Island population of the P. palmeus species group.